Replication regulation of Vibrio cholerae chromosome II involves initiator binding to the origin both as monomer and as dimer - Jha, Jyoti K. (Oxford University Press, 2012)
The origin region of Vibrio cholerae chromosome II (chrII) resembles plasmid origins that have repeated initiator-binding sites (iterons). Iterons are essential for initiation as well as preventing over-initiation of plasmid replication. In chrII, iterons are also essential for initiation but over-initiation is prevented by sites called 39-mers. Both iterons and 39-mers are binding sites of the chrII specific initiator, RctB. Here, we have isolated RctB mutants that permit over-initiation in the presence of 39-mers. Characterization of two of the mutants showed that both are defective in 39-mer binding, which helps to explain their over-initiation phenotype. In vitro, RctB bound to 39-mers as monomers, and to iterons as both monomers and dimers. Monomer binding to iterons increased in both the mutants, suggesting that monomers are likely to be the initiators. We suggest that dimers might be competitive inhibitors of monomer binding to iterons and thus help control replication negatively. ChrII replication was found to be dependent on chaperones DnaJ and DnaK in vivo. The chaperones preferentially improved dimer binding in vitro, further suggesting the importance of dimer binding in the control of chrII replication.